2004
DOI: 10.1158/0008-5472.can-03-1871
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence in Situ Hybridization Map of 6q Deletions in Acute Lymphocytic Leukemia

Abstract: With the objective of identifying candidate tumor suppressor genes, we used fluorescence in situ hybridization to map leukemia-related deletions of the long arm of chromosome 6 (6q). Twenty of 24 deletions overlapped to define a 4.8-Mb region of minimal deletion between markers D6S1510 and D6S1692 within chromosome 6 band q16. Using reverse transcription-PCR, we found evidence of expression in hematopoietic cells for 3 of 15 genes in the region (GRIK2, C6orf111, and CCNC). Comparison between our own and publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 62 publications
3
28
0
3
Order By: Relevance
“…We confirmed heterogeneous deletions of 6q as recurrent events in ALL. These findings concurred with a number of studies using FISH and loss of heterozygosity (LOH), which demonstrated several common regions of deletion involving 6q21-q23 (Jackson et al, 2000;Foroni et al, 2003;Sinclair et al, 2004), further highlighting the importance of this region in ALL pathogenesis while demonstrating that aCGH can be used to accurately delineate regions of CNA in ALL. Even though the cases in this study were highly selected for the absence of established chromosomal abnormalities, a small number were included from other patient subgroups, such as high hyperdiploid and ETV6-RUNX1 positive patients.…”
Section: Discussionsupporting
confidence: 85%
“…We confirmed heterogeneous deletions of 6q as recurrent events in ALL. These findings concurred with a number of studies using FISH and loss of heterozygosity (LOH), which demonstrated several common regions of deletion involving 6q21-q23 (Jackson et al, 2000;Foroni et al, 2003;Sinclair et al, 2004), further highlighting the importance of this region in ALL pathogenesis while demonstrating that aCGH can be used to accurately delineate regions of CNA in ALL. Even though the cases in this study were highly selected for the absence of established chromosomal abnormalities, a small number were included from other patient subgroups, such as high hyperdiploid and ETV6-RUNX1 positive patients.…”
Section: Discussionsupporting
confidence: 85%
“…Ac-Asp + Glu or Met (18) One of the constant products of PSMA enzymatic reaction is glutamate, which might also be a potential modulator and functions through glutamate receptors. Glutamate receptors have been reported to be present in prostate and LNCaP cells as well (19,20). Alternatively, folates, which are produced as a by-product of this enzymatic reaction, could be a potential modulator for PSMA enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…29 Deletions involving 6q are otherwise quite rare in AML, being associated mainly with lymphoid malignancies. [63][64][65] As yet, the target gene(s) is unknown, and because no clear-cut minimally deleted segment was identified (Figure 4), it may prove difficult to identify the genes involved. The losses of 7p and gains of 7q often occurred together in DS-AML, as a consequence of i(7q).…”
Section: Org Frommentioning
confidence: 99%